“Shakespeare is a Finnish national poet:” Developing Finnish Shakespeare Scholarship from the Enlightenment to the Twentieth Century - Southgate, Laina (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
In this article, I will take up the idea of “origins” as it pertains to Finnish Shakespeare during Finland’s time as an autonomous Grand Duchy of Russia from 1809-1917. While not technically the beginning of Shakespearean performances, the late eighteenth and early nineteenth centuries are the beginning of the rhetorical use of Shakespeare in public discourse used to establish cultural sovereignty distinct from Sweden and Russia. Beginning with a brief overview of Shakespearean mentions in the latter half of the eighteenth century, I will analyse the public discourse found in Finnish literary journals and newspaper articles in the 1810’s and 20’s. Following an analysis of J. F. Lagervall’s 1834 Ruunulinna, I will then briefly track how shifting attitudes towards translations such as those found in J. V. Snellman’s writings influenced the emerging Finnish literary and theatre tradition, most notably with Kaarlo Slöör and Paavo Cajendar’s Shakespeare translations and the establishment of the Finnish Theatre in 1871. Finally, an analysis of Juhani Aho’s untranslated essay in Gollancz’ 1916 A Book of Homage to Shakespeare will highlight the legacy of prior Finnish Shakespearean traditions, while also highlighting the limits of translation. Ultimately, I suggest that Shakespeare was appropriated early on as an accessible figure of resistance in the face of Swedish linguistic supremacy and the increasing threat of Russian assimilation and oppression.